Mitochondrial DNA hypomethylation in chrome plating workers. (22nd January 2016) - Linqing, Yang; Bo, Xia; Xueqin, Yang; Hong, Ding; Desheng, Wu; Huimin, Zhang; Gaofeng, Jiang; Jianjun, Liu; Zhixiong, Zhuang
Highlights: MT-TF and MT-RNR1 genes became hypomethylated in chrome plating workers. No change of LINE-1 gene methylation level was observed in chrome plating workers. No change of mitochondrial DNA copy number was observed in chrome plating workers. Abstract: A matched case–control study was conducted to examine the relationship between chromium (Cr) exposure and variation in mitochondrial (mt) DNA methylation. We enrolled 29 pairs of subjects in this study; Cr exposure was confirmed in the cases by detecting blood Cr and other metal ion concentrations. DNA damage caused by Cr exposure was determined in terms of binucleated micronucleus frequency (BNMN) and mtDNA copy number. Finally, a Sequenom MassARRAY platform was applied to inspect the DNA methylation levels of mitochondrially encoded tRNA phenylalanine ( MT-TF ), mitochondrially encoded 12S RNA ( MT-RNR1 ), and long interspersed nucleotide element-1 ( LINE-1 ) genes. The blood Cr ion concentration and micronucleus frequency of the Cr-exposed group were higher than those of the control group, whereas the mtDNA copy number remained unchanged. The methylation levels of MT-TF and MT-RNR1 but not LINE-1 were significantly lower in Cr-exposed workers. Pearson correlation analysis showed that workers with higher blood Cr ion concentrations exhibited lower MT-TF and MT-RNR1 gene methylation, and multiple linear regression analysis indicated that CpG sites 1 and 2 in MT-TF and CpG site 6 in MT-RNR1 were affected. These results suggested that methylation level of mtDNA has the possibility of acting as an alternative effect biomarker for Cr exposure.